1996
DOI: 10.1021/jo9601573
|View full text |Cite
|
Sign up to set email alerts
|

Annelated Dimethyldihydropyrenes. Electrophilic Substitution and Valence Isomerization to Metacyclophanedienes

Abstract: The reversible valence isomerization of cyclophanedienes to dihydropyrenes is discussed for a number of [a]- and [e]-annelated examples, 5 → 6 and 7 → 8, and is related to AM1 and MM2+Pi calculations. Only in [e]-fused systems is the isomerization easily seen to be reversible. Electrophilic substitution of dihydropyrenes is discussed. Nitration of the highly annelated 20 gives a mixture of 8- and 7-nitro derivatives, while NBS/DMF bromination of the benzo[a]dihydropyrene 3 gives mostly 12-bromo derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…As representative examples, we considered metal complexes of the benz[ a ]annulene, 2 , and the cyclopentadienide fused annulene, 5 , to be suitable targets, since [ e ]-fused annulenes such as 6 added the additional complication of easy valence isomerization to the cyclophane-diene isomer 7 . 2b, At the start of this work, no metal complexes of benzannulenes were known. Indeed few metal complexes of any larger annulene were known, probably because of the very limited accessibility and stability of either group of compounds.…”
Section: Synthesesmentioning
confidence: 99%
“…As representative examples, we considered metal complexes of the benz[ a ]annulene, 2 , and the cyclopentadienide fused annulene, 5 , to be suitable targets, since [ e ]-fused annulenes such as 6 added the additional complication of easy valence isomerization to the cyclophane-diene isomer 7 . 2b, At the start of this work, no metal complexes of benzannulenes were known. Indeed few metal complexes of any larger annulene were known, probably because of the very limited accessibility and stability of either group of compounds.…”
Section: Synthesesmentioning
confidence: 99%
“…In other examples, a mixture of 8 and perhaps 4-aryldihydropyrene 9 was observed by 1 H NMR analyses. It was reported that the relative preference for electrophilic substitution in 3 was C2 > C4 > C1 based on the relative heats of formation of the intermediate cations . The relative strain energies of the cationic intermediates may, however, follow a reverse order.…”
Section: Resultsmentioning
confidence: 99%
“…Calculations [21] indicated that the garden flood lamps opened both dhpЈs quickly and gave the bis-cpd 46 (C). Irradiation of this with UV light stable form of the dibenzannulene 52 would be the cyclophane 53 (Scheme 11).…”
Section: Synthesesmentioning
confidence: 99%
“…This is consistent with some of our calculations: While AM1 calculations lated the relative ground state energy differences between the open and closed forms of cis-1,2-diphenylethylene (1 (without CI) do not do a good job on calculating dhp 7 to be bond equal, [22] they do calculate reasonable heats of and 2) (27.3 kcal/mol), 1,2-di(3-pyrrolyl)ethylene (15.5 kcal/ mol), 1,2-di(3-furyl)ethylene (9.2 kcal/mol) and 1,2-di(3-thiformation, H f . [21] The difference in H f (diene-8 Ϫ dhp-7), ∆H f , is calculated to be 3.4 kcal/mol in good agreement enyl)ethylene (Ϫ3.3 kcal/mol). Clearly the thienyl compounds are closest in energy, and appear to make the best with the experimental value of 3 kcal/mol.…”
mentioning
confidence: 92%